2022
DOI: 10.3389/fnut.2022.846378
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Gut Bacteria and Fungi Accompanying Low-Carbohydrate Diet-Induced Weight Loss in Overweight and Obese Adults

Abstract: BackgroundLow-carbohydrate (e.g., Atkins) dietary pattern is one of the most effective diets for weight loss, but little is known about the characteristics of the gut microbiota accompanying low-carbohydrate diets-induced weight loss. This study aims to profile dynamics of gut bacteria and fungi accompanying modified Atkins diets-induced weight loss among overweight and obese adults.MethodsOverweight and obese adults were screened to follow a modified Atkins diet plan (30% of energy from protein, 40% from carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…After adjusting for confounding variables, Parabacteroides were found to be positively associated with BMI_Z in this study. In previous studies, Parabacteroides were usually reported to be significantly increased with a low-carbohydrate diet-induced weight loss in mice models and adults ( Wang et al, 2022 ; Yoshida et al, 2022 ; Yu et al, 2022 ). In this study, although we did not consider the influence of diet, we detected the significant associations between Parabacteroides and BMI_Z, which indicated that the alterations might not be specific to the low-carbohydrate diet reported by Fragiadakis et al (2020) .…”
Section: Discussionmentioning
confidence: 96%
“…After adjusting for confounding variables, Parabacteroides were found to be positively associated with BMI_Z in this study. In previous studies, Parabacteroides were usually reported to be significantly increased with a low-carbohydrate diet-induced weight loss in mice models and adults ( Wang et al, 2022 ; Yoshida et al, 2022 ; Yu et al, 2022 ). In this study, although we did not consider the influence of diet, we detected the significant associations between Parabacteroides and BMI_Z, which indicated that the alterations might not be specific to the low-carbohydrate diet reported by Fragiadakis et al (2020) .…”
Section: Discussionmentioning
confidence: 96%
“…Based on a cross-sectional study on the relationship between the gut microbiota and childhood obesity, Ruminococcaceae_UCG_013 may play an important role in weight loss in children [ 43 ]. Among overweight and obese adults who lost between 5 and 10% of their body weight, Ruminococcaceae_UCG-013 was found to be enriched [ 44 ]. In summary, Ruminococcaceae_UCG-013 may play an important role in weight loss; however, the mechanism by which Ruminococcaceae_UCG_013 affects body weight needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 65 overweight adults were enrolled to follow the Atkins diet for 20–231 days. [ 40 ] Most of the obese adults achieved 5‐10% weight loss and more balanced gut fungi and bacteria. Furthermore, the abundance of Ascomycota reduced while the Basidiomycota increased in those who achieved weight loss.…”
Section: The Interaction Between Diet and Mycobiomementioning
confidence: 99%
“…Yu et al [ 40] 2021 China Atkins diets 20-231 days 65 overweight adults Basidiomycota↑, Ascomycota↓.…”
Section: Introductionmentioning
confidence: 99%